Improving Multi-Floor Factory Facilities Layout Using CRAFT Algorithm Method in UMKM Aneka Songkok Jombang - Firda Amalia Putri; Rusindiyanto Rusindiyanto (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
Facility layout design is a challenging issue in an industry. UMKM Aneka Songkok is a multi-floor building consisting of several departments. Observations show that the placement of work areas does not take into account the relationships between work stations, does not optimise space utilisation, and has an unsystematic material flow. This causes various problems, such as increased material transfer distances and greater occupational safety risks. To address these issues, facility layout improvements are necessary to enhance production effectiveness and efficiency. This study aims to redesign the facility layout of UMKM Aneka Songkok using the Craft algorithm method to improve the layout design, making the facility layout more effective and efficient, thereby organising the production process and minimising material movement distances between workstations. The research results show a reduction in distance per production run of 109.35 m and a reduction in distance per day of production of 387.3 m. The proposed layout was selected because it reduces material movement distances and improves material flow.